Statistical Analysis and Verification of a New Premixed Combustion Model with DNS Data. Issue 11 (1st November 2020) - Hansinger, Maximilian; Pfitzner, Michael; Klein, Markus
ABSTRACT: In this paper, a new analytical premixed flamelet pdf model based on a surrogate reaction source term, is verified with a planar laminar flame and validated using explicitly filtered direct numerical simulation (DNS) data of statistically planar turbulent premixed flames with single-step irreversible Arrhenius chemistry at two different Karlovitz numbers. It is shown that the modeled filtered reaction source term ω ‾ m is in excellent agreement with the one using the Arrhenius source term ω ‾ A for the planar laminar flame over a wide range of filter widths. The model performs also very well on the filtered turbulent DNS data provided that a flame normalized isosurface area Ξ i s o ( c i s o ) is incorporated. Interestingly, the model performance improves with increasing filter widths. This makes it an ideal candidate for high-pressure premixed combustion where usually the filter widths Δ L E S are much larger than the flame's thermal reaction zone thickness δ t h .